Pembuatan Sistem Informasi dengan Analisis dan Perancangan Berorientasi Objek - Pelawi, Dewan (Bina Nusantara University, 2012)
Analysis of business processes by observing the existing system is the main issue to produce information systems according to the needs of the company. Any search of problem solutions when doing business process is performed by a system approach. Object Oriented Analysis and Design (OOAD) is one of the methods currently used to build information systems. The method includes the building of activity diagrams, event table, class diagram, usecase diagrams, usecase description, state chart diagrams, deployment and software architecture, first-cut design class diagram, simple sequence diagram (SSD), sequence diagram (first-cut, view layer, data access layer), communication diagram, updated design class diagram, package diagram, persistent object, and user interface. The results obtained after performing all phases of the method is an information system based on the needs of companies that is expected to improve the performance and effectiveness of the company's business processes and support the business goals.